Ð›ÑŒÐ´Ð¾Ð½ÑƒÐºÐ»ÐµÐ¸Ñ€ÑƒÑŽÑ‰Ð°Ñ Ð°ÐºÑ‚Ð¸Ð²Ð½Ð¾ÑÑ‚ÑŒ Ð³ÐµÐ¼Ð¾Ð»Ð¸Ð¼Ñ„Ñ‹ Upis ceramboides, Ð¾Ð±Ð¸Ñ‚Ð°ÑŽÑ‰ÐµÐ³Ð¾ Ð² Ð¦ÐµÐ½Ñ‚Ñ€Ð°Ð»ÑŒÐ½Ð¾Ð¹ Ð¯ÐºÑƒÑ‚Ð¸Ð¸ - Li, N. G. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2011)
Strategy of cold resistance of Upis ceramboides (Coleoptera: Tenebrionidae) is based on tolerance to freezing, enabling this species to inhabit in extremely cold climate of Yakutia. Frost-tolerance is stipulated by the presence of ice-nucleating proteins in hemolymph, ice-nucleating potential of those are maximum in winter period. Seasonal changes of concentration of polyols in hemolymph affect the value of overcooling temperature, which is higher in spring than in winter. In summer the beetles are sensitive to the temperatures lower those of their supercooling (â€“7.3Â°C), but their tolerance to freezing increases during autumn, starting from August; in December the lower level of lethal temperatures is within the range below â€“83Â°C. The changes in the level of frost-tolerance are tightly related to the seasonal changes in activity and concentration of ice nucleators, as well as polyols.Â